The effectiveness of artificial intelligence models in addressing the concerns of families of children with cerebral palsy: a comparative analysis of ChatGPT, Gemini, and DeepSeek - Erem, Murat; Mercan, Oguz; Yildirim, Savas; Selcuk, Esref; Unyilmaz, Cihan (Frontiers in Pediatrics, 2025)
BackgroundCerebral palsy (CP) is a non-progressive but permanent motor disorder that significantly affects children and their families. With the rise of artificial intelligence (AI)-based information systems, families increasingly use these tools to address their concerns.ObjectiveThis study compared the clinical relevance of responses from ChatGPT, Gemini, and DeepSeek to frequently asked CP-related questions by families.MethodsTen key questions, compiled from reputable medical websites, were posed separately to each AI model. Responses were rated by two independent experts using a 4-point Likert scale, with a third reviewer resolving discrepancies.ResultsGemini achieved the highest mean score (3.2), followed by ChatGPT (2.9) and DeepSeek (2.9). All models provided strong general CP information but underperformed in complex areas such as surgical indications. Gemini gave more structured and comprehensive responses, while ChatGPT and DeepSeek occasionally lacked detail or clarity.ConclusionWhile AI language models can offer useful CP-related information, their reliability in complex clinical decision-making remains limited. Expert oversight is essential, and future systems should integrate multimodal capabilities for improved family guidance and engagement.